Comparing endometrial receptivity array to histologic dating of the endometrium in women with a history of implantation failure. (1st November 2020) - Cohen, Arianne M.; Ye, Xiang Y.; Colgan, Terence J.; Greenblatt, Ellen M.; Chan, Crystal
ABSTRACT: For patients with recurrent implantation failure in IVF, histologic or transcriptomic testing of the endometrium during the mid-secretory phase is often considered. Histological dating of endometrial biopsies (Noyes criteria) can determine if endometrial morphology is consistent with the period of receptivity. Alternatively, endometrial tissue can be sent for a commercial Endometrial Receptivity Array (ERA) test which characterizes the gene expression of the endometrium using a panel of 238 genes that have been implicated in endometrial receptivity. This study aimed to compare the two tests to assess their concordance and to examine the ability of the ERA to successfully predict implantation and pregnancy in a subsequent personalized embryo transfer. A retrospective review was done of 97 patients with a history of implantation failure who underwent an ERA, 35 of whom had histologic dating on the same sample. ERA and histology were classified as 'concordant' when samples were receptive by both tests or non-receptive by both tests. The ERA result was then used to personalize the embryo transfer day, and pregnancy rates from the first subsequent frozen transfer cycle were analyzed. The results indicated that there is poor concordance between ERA and histological dating with only 40.0% agreement and a kappa (95%CI) = −0.18 (−0.50, 0.14). According to the ERA, 48.5% of biopsies were receptive, 47.4% were non-receptive and 2.01% were insufficient tissue for analysis. The clinical pregnancy rate in patients shown to be receptive by ERA was 26.7% and non-receptive was 22.5% following the subsequent personalized ET (p = 0.66). This study concludes that there is a high degree of discordance between histological dating of the endometrium and molecular analysis by ERA. There was no evidence of clinical benefit when embryo transfer was personalized according to ERA in patients with a history of implantation failure.